2008
DOI: 10.1037/a0012584
|View full text |Cite
|
Sign up to set email alerts
|

Does marriage and relationship education work? A meta-analytic study.

Abstract: In this meta-analytic study, the authors examined the efficacy of marriage and relationship education (MRE) on 2 common outcomes: relationship quality and communication skills. A thorough search produced 86 codable reports that yielded 117 studies and more than 500 effect sizes. The effect sizes for relationship quality for experimental studies ranged from d = .30 to .36, while the communication skills effect sizes ranged from d = .43 to .45. Quasi-experimental studies generated smaller effect sizes, but these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

29
456
13
10

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 466 publications
(508 citation statements)
references
References 86 publications
29
456
13
10
Order By: Relevance
“…Such an instructional theory as the core element of an effective intervention program would be necessary for our assessment approach, especially because existing relationship programs suffer from small effects. Hawkins, Blanchard, Baldwin, and Fawcett (2008) found within their meta-analysis small effect sizes (d = .30 to .36) of such programs on relationship quality.…”
Section: Discussionmentioning
confidence: 99%
“…Such an instructional theory as the core element of an effective intervention program would be necessary for our assessment approach, especially because existing relationship programs suffer from small effects. Hawkins, Blanchard, Baldwin, and Fawcett (2008) found within their meta-analysis small effect sizes (d = .30 to .36) of such programs on relationship quality.…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies to determine the important factors influencing long-term relationship between husband and wife (Stutzer & Frey, 2006;Hawkins et al, 2008;Waller & Peters, 2008). There are many studies on marital satisfaction and the influencing factors on this issue.…”
Section: Introductionmentioning
confidence: 99%
“…The goals are to teach couples skills that are believed to be relevant for maintaining a good relationship and to prepare couples for probable future problems and challenges in their relationship. Reviews of RE studies that have been published in the last two decades indicate that under certain conditions RE can change couples' interaction patterns and produce moderate improvements in the adaptation and stability of relationships (Carroll & Doherty, 2003;Christensen & Heavey, 1999;Guerney & Maxson, 1990;Hahlweg & Markman, 1988;Halford, Petch, & Creedy, 2010;Hawkins, Blanchard, Baldwin, & Fawcett, 2008;Markman & Hahlweg, 1993;Pinquart & Teubert, 2010;Schulz, Cowan, & Cowan, 2006;Stanley, Amato, Johnson, & Markman, 2006), but there has been some controversy as to the strength and duration of these effects.…”
mentioning
confidence: 99%
“…However a meta-study by Hawkins et al (2008) found attenders in RE programs to score lower on relationship quality and communication skills than non-attenders, indicating a compensation effect in which high-risk couples are overrepresented in attendance. Thus, the extent to which various risk factors are related to RE participation remains unclear.…”
mentioning
confidence: 99%